If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 18 = 6x + 4 Reorder the terms: 18 + 2x = 6x + 4 Reorder the terms: 18 + 2x = 4 + 6x Solving 18 + 2x = 4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 18 + 2x + -6x = 4 + 6x + -6x Combine like terms: 2x + -6x = -4x 18 + -4x = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 18 + -4x = 4 + 0 18 + -4x = 4 Add '-18' to each side of the equation. 18 + -18 + -4x = 4 + -18 Combine like terms: 18 + -18 = 0 0 + -4x = 4 + -18 -4x = 4 + -18 Combine like terms: 4 + -18 = -14 -4x = -14 Divide each side by '-4'. x = 3.5 Simplifying x = 3.5
| 2(s-4)=-19 | | 23x+6-25x=3-5 | | (4/9)3=32/243 | | d^2+14d+13= | | 3-3=15x+9x | | 2x^2+8=10 | | 9x+2=2x+9 | | 88=4t-15t | | d^2-13d+36= | | 1=2y+5 | | 9x+12=102 | | 2v+xy=w | | 20-45=3(x-3)-7 | | 7m+20=-17m-18 | | d^2+17d+30= | | n+6*n-4=100 | | 10x^2-x-3= | | (-8)+(-23)= | | m^2-8m+12= | | 3a+2b=7200 | | 20+(-41)= | | 4(x*x)-17x+13=-5x+8 | | (-63)-(-79)= | | (-43)-71= | | m^2-6m+8= | | 5/6*42 | | 84-(-37)= | | (-56)+91= | | 56/6*42 | | 2m+5=2m-3 | | (-39)+47= | | 6(x*x)+49x-45=0 |